A Novel Nonsense INS Mutation Causes Inefficient Preproinsulin Translocation Into the Endoplasmic Reticulum - Yang, Ying; Shu, Hua; Hu, Jingxin; Li, Lei; Wang, Jianyu; Chen, Tingting; Zhen, Jinyang; Sun, Jinhong; Feng, Wenli; Xiong, Yi; Huang, Yumeng; Li, Xin; et al. (Frontiers in Endocrinology, 2022)
Preproinsulin (PPI) translocation across the membrane of the endoplasmic reticulum (ER) is the first and critical step of insulin biosynthesis. Inefficient PPI translocation caused by signal peptide (SP) mutations can lead to β-cell failure and diabetes. However, the effect of proinsulin domain on the efficiency of PPI translocation remains unknown. With whole exome sequencing, we identified a novel INS nonsense mutation resulting in an early termination at the 46th residue of PPI (PPI-R46X) in two unrelated patients with early onset diabetes. We examined biological behaviors of the mutant and compared them to that of an established neonatal diabetes causing mutant PPI-C96Y. Although both mutants were retained in the cells, unlike C96Y, R46X did not induce ER stress nor form abnormal disulfide linked proinsulin complexes. More importantly, R46X did not interact with co-expressed wild-type (WT) proinsulin in the ER, did not impair proinsulin-WT folding, trafficking, and insulin production. Metabolic labeling experiments established that, despite with an intact SP, R46X failed to be efficiently translocated into the ER, suggesting that proinsulin domain downstream of SP plays an important unrecognized role in PPI translocation across the ER membrane. The study not only expends the list of INS mutations associated with diabetes, but also provides genetic and biological evidence underlying the regulation mechanism of PPI translocation.